A systematic review of reported outcomes and outcome measures in randomized controlled trials on apical prolapse surgery. Issue 1 (22nd February 2019) - de Mattos Lourenço, Thais Regina; Pergialiotis, Vasilis; Durnea, Constantin; Elfituri, Abdullatif; Haddad, Jorge Milhem; Betschart, Cornelia; Falconi, Gabriele; Doumouchtsis, Stergios K.; ,
Abstract: Background: Evidence on efficacy and safety of pelvic organ prolapse interventions is variable, and methodological flaws preclude meaningful synthesis of primary research data. Objective: To evaluate variations in reported outcomes and outcome measures in randomized controlled trials (RCTs) on apical prolapse surgical interventions. Search strategy: We searched Cochrane, EMBASE, MEDLINE, and Scopus for English‐language articles published from inception to September 30, 2017, using the terms "management", "repair", "operation", and "pelvic organ prolapse". Selection criteria: RCTs on apical prolapse surgical treatment. Data collection and analysis: Outcomes and outcome measures were identified and categorized into domains. Studies were evaluated for quality of outcomes. Descriptive statistics were used to calculate frequencies. Main results: Forty‐three RCTs were included. Seventy‐six outcomes and 66 outcome measures were identified. Bladder and ureteric injury were the most commonly reported intraoperative complications (19/31 studies; 61%). Quality of life was assessed by 19 different instruments and questionnaires. Fourteen (45%) of 31 studies used recurrence of prolapse as a postoperative anatomical outcome. Conclusions: Substantial variation in reported outcomes and outcome measures was confirmed, precluding comparisons across trials and synthesis of the results. Development of a core outcome set will enable high‐quality meta‐analyses to be performed in the future. PROSPERO registration: CRD42017062456. Abstract : We reviewed variations on reported outcomes and outcome measures in apical prolapse interventions. Development of a core outcome set is warranted based on our results.